Prosthesis on prosthesis: three-fourth metal crowns—a novel approach for metallic occlusion. (11th October 2013) - Pachore, Nivedita; Patel, Jayanti R; Sethuraman, Rajesh; Prajapati, Paranjay
Abstract : Single complete denture is a common occurrence which needs special attention in treatment. Denture reinforcement with metallic occlusion is recommended to prevent fracture of denture and wearing of artificial teeth. Various methods have been reported in the literature for metallic occlusion, which either compromise on aesthetics of the premolar teeth or need repeated procedures. This case reports the use of three-fourths metal crowns to achieve metallic occlusions in single complete denture.